PENERAPAN ALAT FERMAS KECE (FERMENTOR MASIN MAKANAN KHAS SUMBAWA DENGAN SISTEM KENDALI CERDAS) DI DESA JOTANG KABUPATEN SUMBAWA - Nurul Hudaningsih; Sopyan Ali Rohman; Iksan Adiasa (Universitas Mataram, 2022)
Masin is a Sumbawa traditional food made from rebon shrimp which is given special spices and then fermented for about 14 days. Masin production often fails because the fermentation process is susceptible to contamination by bacteria and other fungi from the raw materials and the lack of hygiene in the equipment used. In addition, rebon shrimp is a catch of fishermen which is available at a certain time so the masin production must be optimized when the availability of the rebon shrimp is abundant by accelerating the fermentation process. Therefore, it is necessary to apply a Masin Fermenter with an intelligent control system to optimize the masin fermentation process. In addition, it is necessary to standardize the masin production process to reduce the risk of production failure. The social activity is carried out through workshops and discussions with masin entrepreneurs. Workshop materials include: How to make the fermenter and how to use the masin fermenters; Dissemination of Standard Operating Procedures (SOP) for Masin production. Masin production with FERMAS-KECE is better than traditional method in terms of color, taste and aroma. The Masin fermentation process with FERMAS-KECE is faster than traditional method. The fermentation process has decreased after 3-5 which indicates the process has been completed so that with this it can increase production capacity up to 300%. In addition, the application of SOP for the manufacture of masin can reduce the risk of failure in masin production and the quality of standardized masin with uniform quality in each production process. Based on the results of the evaluation of participant satisfaction, it was found that the participants were very satisfied, both in terms of the material, the way the material was delivered and the fermenter machine used was very useful and needed by participants. Therefore, the application of FERMAS-KECE and SOP during the masin production process can increase the productivity, efficiency and quality of the masin.